2020
DOI: 10.1007/s00330-020-06977-5
|View full text |Cite
|
Sign up to set email alerts
|

Acute pulmonary embolism in non-hospitalized COVID-19 patients referred to CTPA by emergency department

Abstract: Objectives To evaluate the prevalence of acute pulmonary embolism (APE) in non-hospitalized COVID-19 patients referred to CT pulmonary angiography (CTPA) by the emergency department. Methods From March 14 to April 6, 2020, 72 non-hospitalized patients referred by the emergency department to CTPA for COVID-19 pneumonia were retrospectively identified. Relevant clinical and laboratory data and CT scan findings were collected for each patient. CTPA scans were reviewed by two radiologists to determinate the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
89
5
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(110 citation statements)
references
References 30 publications
6
89
5
6
Order By: Relevance
“…One in five patients included in this study had PE on admission, in good agreement with the reported prevalence of PE on CTPA performed for COVID-19 at the emergency department [ 16 ]. The remaining cases of PE occurred throughout the hospitalization for COVID-19, again consistently with other investigations [ 7 – 9 , 11 ].…”
Section: Discussionsupporting
confidence: 86%
“…One in five patients included in this study had PE on admission, in good agreement with the reported prevalence of PE on CTPA performed for COVID-19 at the emergency department [ 16 ]. The remaining cases of PE occurred throughout the hospitalization for COVID-19, again consistently with other investigations [ 7 – 9 , 11 ].…”
Section: Discussionsupporting
confidence: 86%
“…After excluding duplicates and preliminary screening, 151 full-text articles were assessed for eligibility and 130 studies were excluded for not meeting the inclusion criteria, leaving 23 investigation fulfilling the inclusion criteria ( Fig. 1) [1,3,4,8,12,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
“…Coagulopathy is one of the most concerning sequelae in COVID-19 patients. Several reports have shown mortality associated with pulmonary emboli and venous thrombosis in severely ill COVID-19 patients (192)(193)(194)(195)(196)(197)(198)(199). Interestingly, a study by Wichmann et al described the results of 12 mandatory autopsies of COVID-19, PCR confirmed patients.…”
Section: Comparison Of Cardiovascular Conditions Associated With Sarsmentioning
confidence: 99%